Trichoderma harzianum (Th Azad): A Promising Bio-control Agent Against Lentil Wilt - Singh, Anuradha; Srivastava, Mukesh; Shahid, Mohammad; Pandey, Sonika; Trivedi, Shubha; Kumar, Vipul; Kumar, Yatindra (International Journal of Bio-resource and Stress Management, 2023)
Biological control is an eco-friendly approach for the management of crop diseases. Trichoderma isolate (Th azad), isolated from field soil is a new potential local isolate identified as Trichoderma harzianum. Trichoderma isolate (Th Azad) was tested against lentil wilt pathogen Fusarium oxysporum f. sp. lentis (Fol) for it’s abiotic stress tolerance and its antagonistic potential both in vitro and in vivo conditions. Th. Azad effectively inhibited the growth of Fol (69.23%) under in vitro and field conditions against the seven seed quality attributes viz. germination, shoot length, root length, seedling length, seedling dry weight, vigour index I and vigour index II. Treatment (Th Azad+Vitavax) was found to be significantly superior and effective as it has increased germination of lentil by 8.26% over control. Trichoderma isolate(Th Azad) was identified by morphological and molecular characterization using 18S rRNA gene sequence with the help of a universal Internal Transcribed Spacer (ITS) marker that gives an amplicon of a total of 1173 base pairs that is later sequenced and allotted with Gene Bank Accession no. JX119211. So, Th Azad is a potential abiotic stress tolerant isolate and can be used for effective management of wilt disease with quality yield of lentil crop when applied as seed dresser at a concentration of 5 g kg-1 under field conditions.